Implementasi Metode Pembelajaran Variatif Dalam Meningkatkan Pemahaman Siswa Kelas XII Pada Mata Pelajaran Ilmu Faraid Di Madrasah Diniyah Muadalah Aliyah Nurul Qarnain Baletbaru Tahun Pelajaran 2023/2024 - Widodo, Ari Dwi; Khoirunnisa, Arida (Cendekia : Jurnal Pendidikan dan Keagamaan, 2024)
This research was motivated by the application of the bandongan method in learning Faraid science using the book I’natul Talib Fi’ Bidayati Ilmi Faraid written by Sayyid Ahmad bin Yusuf bin Muhammad Al-Ahdal which was considered less effective in increasing students’ understanding. The aim of the research is to describe the implementation and supporting and inhibiting factors of a varied learning method that combines the bandongan method to improve the understanding of class XII students at MDMA Nurul Qarnain Baletbaru for the 2023/2024 academic year. This research uses qualitative methods with field and descriptive research types, to collect data through interviews, observation and documentation. As well as data analysis using the Miles Huberman technique, namely through data reduction, data presentation and drawing conclusions. The results of the research show that teachers prepare teaching materials, semester plans and infrastructure, as well as apply the bandongan method and variations of the rote method to help strengthen understanding of the material, while the question and answer method and group discussion are applied at the end of the lesson to find out the extent of students’ understanding. Supporting factors are the availability of supporting books and special Islamic boarding school curricula, while inhibiting factors include limited allocation of learning time and a lack of learning aids such as understanding Arabic vocabulary and counting.